EVALUASI MUTU DODOL DENGAN VARIASI PENAMBAHAN BUAH JAMBU BIJI MERAH(Psidium guajava L.,) DAN GULA PASIR (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this study was to determine the best addition of red guava fruit (Psidium guajava l.,) and sugar to wards the quality of fruit dodol. The experiment was arranged by the Randomized Complete Design (RCD) with four treatments and four replications treatment. The treatments is G1J1 (80% sugar : 20% red guava fruit), G2J2 (76% sugar : 24% red guava fruit), G3J3 (72% sugar : 28% red guava fruit) and G4J4 (68% sugar : 32% red guava fruit). Data obtained  treated by the analysis of variance followed by Duncan’s NewMultiple Range Test (DNMRT) the level of 5%. The result of this study showed the ratio of red guava fruit and sugar affected on water content, ash content, crude fiber content, sucrose levels, colour, flavor, taste, texture and overall acceptance of fruit dodol. It was concluded the treatment of G4J4 (68% sugar : 32% red guava fruit) produce dodol with the best quality towards: water content 15.47%; ash content 0.41%; crude fiber content 13.67% and sucrose levels 45.04% andin terms ofacceptable of organolepticassessmentbypanelists. Keywords: Dodol,red guava  fruit, and sugar.